Perkembangan Teater di Bali melalui Sosok Dramawan Abu Bakar - Darma Putra, I Nyoman (Jurnal Kajian Bali (Journal of Bali Studies); Vol 3 No 1 (2013): PENULISAN SEJARAH BALI, 2013)
Abstract A Western-style of theatre has developed in Bali since the turnof the twentieth century, but it has rarely attracted scholarly attention. Studies on the performing arts in Bali have mainly focused on Balinese (traditional) dance and drama. This should come as no surprise given that Balinese dance and drama have developed as a broad and inseparable part of Balinese custom and religious practice. Against this phenomena, this article traces the development of Western-style theatre in Bali through the artistic activities of the prominent playwright, performer and director, Abu Bakar. From the 1960s until the present, Abu Bakar has been an active promoter of Westernsty letheatre in Bali as well as in the main cities of Java andeven in Singapore. He has also has helped students and theatre groups around Bali to study and perform theatre. Initially, Abu Bakar established his own theatre group, Poliklinik, which hascontinued to stage performances as well as collaborating with young people or student theatre study clubs. His extensiverecord of artistic activity has been recorded in newspaper reports and reviews and these form the main source of documentation in this article. By examining qualitative data collected from newspaper archives and interviews, including with Abu Bakar, this article proposes a contemporary historyof theatre or modern drama in Bali.
Keywords: Bali, theatre, modern performing arts, traditional performing arts, modern drama.